2021
DOI: 10.1177/2192568221991515
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Plate-Screws and Lower Postoperative T1 Slope Affect Cervical Allospacer Failures in Multi-Level ACDF Surgery: Anterior Versus Posterior Fixation

Abstract: Study Design: Prospective observational study. Objective: In ACDF, graft failure and subsidence are common complications of surgery. Depending on the cervical fixation, different biomechanical characteristics are applied on the grafts. This aims to describe the incidence of cervical spacer failure in patients with cervical degenerative condition according to the cervical fixation method and sagittal balance. Method: From November 2011 to December 2015, 262 patients who underwent cervical spine surgery were enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Suk et al demonstrated that allospacer failure commonly occurs at a location where the allograft is not protected by plate or screw fixation. 37 Furthermore, Lee et al suggested that using a screw length that is > 75% of the vertebral body length is needed to decrease pseudarthrosis. 38 Second, choosing an appropriate graft height to avoid overdistraction is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Suk et al demonstrated that allospacer failure commonly occurs at a location where the allograft is not protected by plate or screw fixation. 37 Furthermore, Lee et al suggested that using a screw length that is > 75% of the vertebral body length is needed to decrease pseudarthrosis. 38 Second, choosing an appropriate graft height to avoid overdistraction is needed.…”
Section: Discussionmentioning
confidence: 99%
“…This slightly flexed posture of the neck lengthened the posterior cervical muscles, thereby making its depth shallower, and thus, performing the anterior surgery after the posterior surgery made positioning the neck in that manner more convenient. PAP surgery also was favorable if an all-pedicle screw construct was preferred, especially in patients with osteoporosis, severe deformity, and large enough pedicles (≥3.5 mm) [ 6 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the general condition of the patients is related to the preoperative and postoperative recovery of function, the overall condition of the patients is an important factor [ 42 , 43 ]. Additionally, we included more severe spondylotic myeloradiculopathic cases that had undergone combined anterior–posterior surgery [ 44 , 45 , 46 ], and as such the rate of combined anterior–posterior surgeries was much higher than that in another study [ 5 ]. Moreover, we report not only actual falls but also the objective measures of functional mobility tests and HGS, which all affect patient subjective symptoms.…”
Section: Discussionmentioning
confidence: 99%